Acidic Pyridinium Inner Salt as a New, Effective and Reusable Catalyst for the One-Pot Three-Component Synthesis of N-substituted 5-aryl-4-benzoyl- 3-hydroxy-3-pyrrolin-2-ones in Aqueous Media - Shahnaei, Roya; Kabirifard, Hassan (Current Organocatalysis, 2021)
Background: The present method is facile and effective for the synthesis of N-substituted 5-aryl-4-benzoyl-3-hydroxy-3-pyrrolin-2-one derivatives which are obtained by one-pot threecomponent condensation reactions of aromatic aldehydes, primary amines and ethyl benzoylpyruvate in the presence of a novel homogeneous catalyst including acidic pyridinium inner salt (PIS) at 50°C in ethanol and water mixture as solvent. Methods: 5-Aryl-4-benzoyl-3-hydroxy-3-pyrrolin-2-ones were synthesized through a one-pot three- -component tandem formation of Schiff base cyclo condensation reaction of aromatic aldehydes, primary amines and ethyl benzoylpyruvate in the presence of 10 mol% of acidic pyridinium inner salt as a catalyst under aqueous ethanol medium at 50°C. All obtained structures were confirmed by their elemental analysis data and IR, 1H NMR and 13C NMR spectroscopy. Results: Three-component synthesis of 5-aryl-4-benzoyl-3-hydroxy-3-pyrrolin-2-ones catalyzed by acidic pyridinium inner salt with aromatic aldehydes, primary amines and ethyl benzoylpyruvate in aqueous ethanol medium at 50°C was prepared. The achieved derivatives (eight entries) were well synthesized in excellent yields. Conclusion: We found acidic pyridinium inner salt as a proper catalyst for this method. A catalyst’s novelty is excellent catalytic activity, easy separation of the reaction mixture by washing with cold water and reusability of the catalyst for six consecutive periods without disrupting the activity of this catalyst system.
Keywords: antiinflammatory